The Implementation Of The Characters Education To The Early Childhood Based On Akidah (4-6 Years Old) In Tk Khalifah 29 Surakarta - Setyaningrum, Eka Ari (BELIA: Early Childhood Education Papers, 2017)
This education aims to build human resources that not only develop in academic, but also the guidance of the studentsâ mental. One of the students mental guidance is for giving characters education. Islam is one of the basics can be used in implementing the characters education in school can integrate the characters education into the curriculum based on islamic. This research aims to find  the information about the implementation of the characters education in preschool that has the curriculum based on Islamic. This study aims to describe the implementation of the characters education based on the akidah and to know the problems and  the supporting factors of the implementation of the characters education in early childhood (4-6 years old) in TK Khalifah 29 Surakarta. The research applies a qualitative descriptive study. This research is located in TK Khalifah, Number 29, Surakarta. A headmaster and the teachers of the class A group and class B group as informant. In this research, data was collected by the observations, interviews, and documentations. The validity of this research is using triangulation and the steps of the analysis by Miles and Huberman method, that is data collection, data reduction, data presentation and the last drawing conclusion. The results of this research are the characters education of this TK was applied by intergrating the curriculum of the tauhid and the entrepreneurship into three steps of the characters education, planning, implementation, and evaluation by using habituations, exemplarys, disciplinaries, direct practices, assignments, and conversations. The implementation of the characters education based on aqidah have problems, such as 1) parents who have different visions and goals with the schools and parents who are less attention to their children 2) the lack of the teachersâ creativity in making RPPH 3) the age of the children. While for the supporting factors, such as the parentsâ support, societies and the professional teachers and infrastructure facilities adequately.  Keywords: Character Education, Akidah, Early Chilhood